Comprehensive Analyses of Glucose Metabolism in Glioma Reveal the Glioma-Promoting Effect of GALM - Xu, Jiacheng; Guo, Yuduo; Ning, Weihai; Wang, Xiang; Li, Shenglun; Chen, Yujia; Ma, Lixin; Qu, Yanming; Song, Yongmei; Zhang, Hongwei (Frontiers in Cell and Developmental Biology, 2022)
Glioma is the most common tumor with the worst prognosis in the central nervous system. Current studies showed that glucose metabolism could affect the malignant progression of tumors. However, the study on the dysregulation of glucose metabolism in glioma is still limited. Herein, we firstly screened 48 differentially expressed glucose metabolism-related genes (DE-GMGs) by comparing glioblastomas to low-grade gliomas. Then a glucose metabolism-related gene (GMG) based model (PC, LDHA, GUSB, GLB1, GALM, FBP1) was constructed by PPI network and Lasso regression. Thereinto, the high-risk group was encountered with a worse prognosis than the low-risk group, and M2 Macrophage was positively relevant to risk score. Various classical tumor-related functions were enriched by GO and KEGG analyses. Since protein GALM was rarely studied in glioma, we detected high expression of GALM by western blot and immunohistochemistry in glioma tissues. And experiments in vitro showed that GALM could promote the EMT process of glioma cells and could be regulated by TNFAIP3 in glioma cells. Overall, our study revealed the critical role of glucose metabolism in the prognosis of patients with glioma. Further, we demonstrated that GALM was significantly related to the malignancy of glioma and could promote glioma cells’ EMT process.